The Early Awareness and Alert System in Sweden: History and Current Status - Eriksson, Irene; Wettermark, Björn; Persson, Marie; Edström, Morgan; Godman, Brian; Lindhé, Anna; Malmström, Rickard E.; Ramström, Helena; von Euler, Mia; Bergkvist Christensen, Anna (Frontiers in Pharmacology, 2017)
Introduction: Over the past decades, early awareness and alert (EAA) activities and systems have gained importance and become a key early health technology assessment (HTA) tool. While a pioneer in HTA, Sweden had no national level EAA activities until 2010. We describe the evolution and current status of the Swedish EAA System. Methods: This was a historical analysis based on the knowledge and experience of the authors supplemented by a targeted review of published and grey literature as well as documents relating to EAA activities in Sweden. Key milestones and a description of the current state of the Swedish EAA System is presented. Results: Initiatives to establish a system for the identification and assessment of emerging health technologies in Sweden date back to the 1980s. Since the 1990s, the Swedish Agency for Health Technology Assessment and Assessment of Social Services (SBU) supported the development of EuroScan and was one of its founder members. In the mid-2000s, an independent regional initiative, driven by the Stockholm County Drug and Therapeutics Committee, resulted in the establishment of a regional horizon scanning function. By 2009, this work had expanded to collaboration between the four biggest counties in Sweden. The following year it was further expanded to the national level and since then the Swedish EAA System has been carrying out identification, filtration and prioritization of new medicines, early assessment of the prioritized medicines, and dissemination of information. In 2015, the EAA system was incorporated into the Swedish national process for managed introduction and follow-up of new medicines. Outputs from the EAA system are now used to select new medicines for inclusion in this process. Conclusions: The Swedish EAA System started as a regional initiative and rapidly grew to become a national level activity. An important feature of the System today is its complete integration into the national process for managed introduction and follow-up of new medicines. The System will continue to evolve as a response both to the changing landscape of health innovations and to new policy initiatives at the regional, national and international levels.